Corporalidad y empoderamiento de las mujeres. La danza del vientre en Quito - Campaña Santacruz, Camila Matilde (2014)
This research is based on experiences of life of a group of bellydancers and their process of body appropriation and empowerment through dance. This work argues there are other ways of women empowerment which are related with the women´s body appropriation, expression of feminity and capability of manage their own life. In the first part I will show the context of the practice of bellydance in Middle East and Quito. The second part, describes the process of body appropriation. In the third part, the objective is to show how women dancers have reached the empowerment: how they overcame gender prejudices and how they reach the control their own life. The theoretical approaches come from of some feminist theories: ecofeminism and the concept of empowerment. The methodologies come from anthropology: participant observation and depth interviews.